Porous Versus Nonporous Orbital Implants After Enucleation for Uveal Melanoma: A Randomized Study - Ho, Vivian W M; Hussain, Rumana N; Czanner, Gabriela; Sen, Julia; Heimann, Heinrich; Damato, Bertil E (Ophthalmic plastic and reconstructive surgery, 2017)
To compare hydroxyapatite with acrylic implants after enucleation for uveal melanoma with respect to eyelid position, ocular motility, implant complications, and patient satisfaction. Patients undergoing primary enucleation for uveal melanoma between May 2005 and November 2012 at the Liverpool Ocular Oncology Centre, United Kingdom, were randomized between hydroxyapatite and acrylic implants. Questionnaires were sent to patients and ocularists to comment on the main outcomes. A total of 416 patients were recruited in the study, of whom 281 were included, with 49.5% (139/281) and 50.5% (142/281) receiving a hydroxyapatite (HA) or acrylic (AC) implant. Mailed questionnaires completed at ≥18 months by patients showed no significant differences between the groups in eyelid position, prosthetic motility, socket complications, and patient satisfaction. Complications included implant extrusion (1% vs 4%), enophthalmos (26% vs 26%), and superior sulcus deformity (24% vs 24%) with HA and AC implants, respectively, (Fisher exact test p > 0.0125 in all, Bonferroni correction). Questionnaires completed by ocularists indicated no significant differences in eyelid opening, prosthetic motility, and other complications at 6 months (Fisher exact test, p > 0.05 in all); there was a higher prevalence of ptosis with AC than HA implants (46% vs 25%, p = 0.03) and a greater need for ocularists' treatment with HA than AC (50% vs 28%, p = 0.03). Patient-reported outcomes after enucleation for uveal melanoma indicate no major differences between hydroxyapatite and acrylic implants in surgical outcomes and patient satisfaction. There was a higher prevalence of ptosis with AC and a greater need of ocularists' visits with HA at around 6 months observed by ocularists.